ANALISIS SKALA USAHA DAN TINGKAT KEUNTUNGAN INDUSTRI KERAJINAN SONGKET DI KOTA PALEMBANG - Abu Kosim; Azwardi Azwardi (Department of Development Economics, Universitas Sriwijaya, 2008)
This research is purposed to know the the production scale and profit condition of songket industry in Palembang. By using The Constant Elasticity Supply, especially based on the value of homogenity h we can know the production scale is constant returns to scale and so the industrial profit is maximized. Key Words: Production scale, Profit condition of songket industry.